Feeding Behavior Among Stunting Toddler’s Mothers - Silvia Farhanidiah; Yuni Sufyanti Arief; Iqlima Dwi Kurnia (Pediomaternal Nursing Journal, 2021)
Introduction: Stunting is the accumulation of nutritional deficiency in a long time. This research has the objective to describe the knowledge, attitude, and action of feeding in stunting toddlers mothers in the Work Area of Tambak Wedi Public Health Center Surabaya.Methods: A descriptive observational study design was used. The population of this research was mothers who have stunting toddlers with total of 65 respondents. The sample total of this research was 60 respondents proportional sampling technique. The data was analyzed using descriptive analysis.Results: The result of this research shows that 37 respondents (61.6%) have less knowledge, 44 respondents (58.3%) have negative attitude and 35 respondents (58.3%) have inappropriate action.Conclusion: Behavior of feeding by the mother affects the status of the toddler, so it needs to increase mother’s knowledge, attitude, and  action about feeding in toddlers. This research suggests that Public Health Center should provide information about feeding to stunting toddlers through health promotion activity.